Flavor quality characteristics of Sichuan Xiaoqu Baijiu from different production areas - XU Yuecheng, LUO Yue, ZHONG Ciping, HE Yuan, WU Yinghuan, YI Xin, CHEN Yanmei (Zhongguo niangzao)
In order to study the flavor and quality characteristics of Sichuan Xiaoqu Baijiu (numbered as JJ, PZ, LZ, NC, LC, SL, QX, MS), the volatile flavor compounds of Xiaoqu Baijiu samples from different production areas (Chongqing Jiangjin, Sichuan Pengzhou, Luzhou, Nanchong, Shuangliu, Quxian, Meishan) were analyzed by gas chromatography-quadrupole time-of-flight mass spectrometry (GC-QTOF-MS). Combined with orthogonal partial least square discriminant analysis (OPLS-DA), the key aroma substances (OAV>1) and key differential flavor substances (VIP≥1, P<0.05) were screened by odor activity value (OAV) and variable importance projection (VIP) values. The results showed that 98 kinds of volatile flavor compounds were identified in Xiaoqu Baijiu samples from different production areas, including 28 kinds of common volatile flavor compounds and 11 kinds of characteristic flavor substances (detected in only one sample). The ratios of main volatile flavor substances in Xiaoqu Baijiu samples from different production areas were significantly different (P<0.05). Using the ratio of isoamyl alcohol/n-propanol and isoamyl alcohol/isobutanol, the quality of Sichuan Xiaoqu Baijiu was identified. A total of 46 key flavor substances and 17 key differential flavor substances were screened. The 17 key differential flavor substances were compared with 10 key aroma substances all detected in Xiaoqu Baijiu from different production areas, and 7 kinds of signature aroma compounds were selected which led to the quality difference of Sichuan Xiaoqu Baijiu from different production areas.